Fate of stable hips after prophylactic femoral varization osteotomy in patients with cerebral palsy - Sung, Ki Hyuk; Kwon, Soon Sun; Chung, Chin Youb; Lee, Kyoung Min; Kim, Jaeyoung; Lee, Seung Yeol; Park, Moon Seok (BMC Musculoskeletal Disorders, 2018)
Background: Concurrent prophylactic femoral varization osteotomy (FVO) for stable hips has been performed in patients with cerebral palsy (CP) undergoing hip reconstructive surgery for the contralateral displaced hip. However, there is currently a lack of studies investigating the outcome after the prophylactic FVO in stable hip. This study investigated the outcomes after FVO in stable hips with CP and influencing factors. In addition, this study compared the outcomes with those after hip reconstructive surgery in the contralateral displaced hip. Methods: This study included 119 CP patients with 224 hips (80 stable, 144 displaced) undergoing hip reconstructive surgery including FVO. Migration percentage (MP), neck-shaft angle (NSA), and head-shaft angle (HSA) were measured through preoperative and follow-up hip radiographs. All hips were divided into the stable (MP ≤ 33%) and displaced hip groups (MP > 33%) according to the preoperative radiographs, and the annual changes in the radiographic indices after FVO were analyzed. Results: In stable hip group, MP did not significantly increase over time (p = 0.057) after prophylactic FVO. In displaced hip group, MP significantly increased over time (1.6%/year, p < 0.001). MP was significantly decreased in cases of concomitant Dega pelvic osteotomy in both stable (14.5%, p < 0.001) and displaced hips (18.9%, p < 0.001). Conclusions: Prophylactic FVO in the stable hip in patients with CP showed good surgical outcomes, without a risk of hip displacement throughout the follow-up duration, while hip reconstructive surgery in the displaced hip was associated with a risk of increased hip displacement.
Keywords: Adolescent; Adult; Cerebral Palsy; Child; Female; Femur; Follow-Up Studies; Hip Dislocation; Humans; Male; Osteotomy; Prophylactic Surgical Procedures; Reconstructive Surgical Procedures; Young Adult; Cerebral palsy; Displaced hip; Hip reconstructive surgery; Prophylactic femoral varization osteotomy; Stable hip